KESEJAHTERAAN ANAK TERKAIT HAK ATAS PERLINDUNGAN DARI LINGKUNGAN YANG MEMBAHAYAKAN DI LOKALISASI PROSTITUSI GANG BOKER, JAKARTA TIMUR: Children's Welfare Related To The Right To Protection From A Harmful Environment In The Localization Of Boker Gang Prostitution, East Jakarta - Khanza Poetri Ferdyan; Maria Silvya Elizabeth Wangga (Faculty of Law, Trisakti University, 2024)
Every child has the same rights, namely the right to welfare. According to Law no. 4 of 1979 Child welfare is